2022
DOI: 10.1140/epjc/s10052-022-11110-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of asymptotically de Sitter black hole in dRGT massive gravity from Rényi entropy

Abstract: The thermodynamic properties of the de Rham–Gabadadze–Tolley (dRGT) black hole in the asymptotically de Sitter (dS) spacetime are investigated by using Rényi entropy. It has been found that the black hole with asymptotically dS spacetime described by the standard Gibbs–Boltzmann statistics cannot be thermodynamically stable. Moreover, there generically exist two horizons corresponding to two thermodynamic systems with different temperatures, leading to a nonequilibrium state. Therefore, in order to obtain the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Rényi entropy can explore the nuances of BH information and its connection to quantum gravity, and it has made a significant impact on the thermodynamics of BHs. It can be calculated as [28],…”
Section: The Impact Of Rényi Entropy On the Thermodynamics Of The Bhmentioning
confidence: 99%
“…Rényi entropy can explore the nuances of BH information and its connection to quantum gravity, and it has made a significant impact on the thermodynamics of BHs. It can be calculated as [28],…”
Section: The Impact Of Rényi Entropy On the Thermodynamics Of The Bhmentioning
confidence: 99%
“…The stability of this massive theory was studied and it was shown that this theory enjoys the absence of the Boulware-Deser ghost [39]. BH solutions in the context of massive gravity and their thermodynamical properties have been studied [40][41][42][43][44][45][46][47][48]. Vegh introduced the dRGT-like massive theories of the different classes by modification in the reference metric.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there are several investigations on the non-extensive nature of the black holes. [58,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] One of the useful choices of the non-extensive entropy is the Tsallis entropy. [81,82] However, by using Tsallis statistics, it is not easy to define a proper temperature which is the state variable based on the notion of maximum entropy.…”
Section: Introductionmentioning
confidence: 99%